Trends and patterns of imports of legal and illegal live corals into the United States. (1st October 2020) - Petrossian, Gohar A.; Sosnowski, Monique C.; Weis, Judith S.
Abstract: Coral reefs are the fundamental building blocks of tropical marine ecosystems. They are also one of the most endangered ecosystems on the planet suffering from a large number of environmental, fishing, and trade threats. However, little research has been done to better understand the trends in illegal imports of live corals into the United States, especially as they relate to legal imports. This research examines the major patterns in the legal and illegal imports of live corals into the United States by analyzing the U.S. Fish and Wildlife Service Law Enforcement Management Information Systems database, along with the Convention on the International Trade in Endangered Species legal trade database, for the 2003–2012 period. The import patterns of illegally harvested live corals into the United States indicated that: (a) three genera ( Euphyllia, Acropora, and Favites) accounted for 26% of all seizures; (b) imports from four countries accounted for slightly over 91% of all seizures; and (c) over 90% of the seizures occurred in five ports of entry. The import patterns of illegally harvested live corals closely mirror those of legal imports when genera and countries of export are examined. Additionally, 10 times more corals were seized in 2012 than in 2003, and legal imports doubled from 2003 to 2009, while both trends leveled in the later few years examined. The study findings suggest that interventions should focus on enhancing law enforcement efforts through capacity building and by establishing reliable channels of communication between the US and the core exporting countries. It is also recommended that US customs focus their inspection efforts on high-risk species, especially at ports that receive these imports from Indonesia, Tonga, Australia, and Fiji. Meanwhile, public education campaigns to raise awareness, as well as the development of regulated coral aquaculture, may lift the pressure and need for illegally harvesting corals from the wild. Highlights: Details the process of illegal coral imports into the United States using a criminological framework. Examines coral seizures at U.S. ports of entry during 2003–2012. Identifies concentrations of seizures by genus, export country, and entry port. Compares legal and illegal import trends by genus and export country.